Gambaran Komunikasi Interpersonal Mahasiswa dengan Dosen Prodi Ners di STIKes Santa Elisabeth Medan Tahun 2021 - Nestariang Laia; Lindawati F. Tampubolon; Ance M. Siallagan (Jurnal Indah Sains dan Klinis, 2022)
Interpersonal communication is a process and effort of individuals or groups in influencing by conveying information or messages intended to other individuals both verbally and nonverbally so that feedback and interactions occur between the two parties as a process of transferring knowledge from lecturers to students. In this investigation, we'll find out the description of interpersonal communication between students and lecturers at the Nursing Study Program of STIKes Santa Elisabeth Medan. This type of research is descriptive research design, the sampling in this study used a total sampling technique, their respondent were 91 people. The results of the research showed that the interpersonal communication of third-level Nurses students with the majority of lecturers was in the pretty good category (94.5%). with the existence of interpersonal communication students with lecturers can be maintained or improved for the better.